Revolutionizing Catechesis: Embracing Technology for Effective Faith Formation - Tarihoran, Emmeria; Firmanto, Antonius Denny; Supur, Agustinus; Kurniawan, Alponsus Zeno (Asosiasi Ahli Filsafat Keilahian Indonesia, 2024)
This literature review explores the transformative integration of technology in faith formation, particularly in catechesis. The shift toward digital platforms prompts a reevaluation of engaging modern learners. This article uncovers technology's advantages and challenges in catechetical contexts by assessing existing literature. Technology enables novel approaches to religious instruction, enhancing learner engagement and comprehension. Interactive tools, online resources, and multimedia enrich accessibility. However, concerns encompass potential superficiality, disruption, and traditional value retention. A balanced method emerges through synthesis, combining proven pedagogies with suitable technology for optimal outcomes. The review highlights the significance of a discerning and empathetic integration of technology in catechesis, fostering genuine spiritual growth within today's technology-immersed generation.